The Pragmatic Strategies of Politeness Principles and Role Balance of Interpreters in Sino-U.S. Diplomatic Negotiations - Bai, Huinian; Tang, Jun (Pacific International Journal, 2025)
This study investigates the pragmatic strategies employed by interpreters in Sino-U.S. diplomatic negotiations, with a specific focus on the application of politeness principles. As interpreters serve not only as linguistic translators but also as cultural mediators, their role is critical in navigating the complexities of communication, particularly during discussions on sensitive political, economic, and social issues. The research evaluates how interpreters balance their responsibilities, ensuring linguistic accuracy and cultural appropriateness while managing the face needs of both negotiating parties. Utilizing case analyses of significant diplomatic events, including the Shanghai Communiqué and Sino-U.S. trade negotiations, the study highlights the strategic use of positive and negative politeness strategies to foster mutual understanding and respect. The findings reveal that interpreters' application of these strategies significantly impacts the effectiveness of diplomatic communication, ultimately influencing negotiation outcomes. The study underscores the essential role of politeness in international relations and its implications for successful diplomatic engagements.